A new model for injury prevention in team sports: the Team-sport Injury Prevention (TIP) cycle. Issue 1 (2nd January 2019) - O'Brien, James; Finch, Caroline F.; Pruna, Ricard; McCall, Alan
ABSTRACT: Recently, there has been growing interest in injury prevention for football and other team sports, including the development of models and frameworks to guide injury prevention efforts. However, many existing models are geared towards the conduct of injury prevention research and do not reflect the everyday injury prevention approach of sports medicine and sports science practitioners working in professional teams. Here, we present a new model, the Team-sport Injury Prevention (TIP) cycle, specifically aimed at the sports team medicine/science practitioner. It involves a simple continual cycle with three key phases: (Re) evaluate, Identify and Intervene . These phases incorporate key aspects of previous models, along with important implementation aspects. By progressing through the model's three phases, team medicine/science practitioners can develop a context-specific and dynamic injury prevention strategy.